Pengembangan Produk Olahan Ikan Patin sebagai Daya Tarik Wisata Kuliner di Masyarakat - Hidayat, Taufik; Erniyanti, Windi Kirana; Hermansyah, Ivan; Purwaningtyas, Azzra Nabila; Hutahaean, Erik Saut Hotoguan (Jurnal Pemberdayaan Pariwisata; Vol 7 No 1 (2025): Jurnal Pemberdayaan Pariwisata, 2025)
RW.18 located in Setia Mekar village has great potential in catfish management, but the local community has not yet understood the concept of value-added processing. This abundant resource has not been utilized optimally to support the tourism sector, especially culinary tourism. This service aims to empower the community in processing catfish into attractive culinary products that have a selling value. The methods used include interviews to identify the conditions and needs of partners, training with culinary experts to introduce various innovative recipes, and hands-on practice in producing processed catfish. This simple implementation is carried out to ensure that knowledge can be easily applied by the community. The results of the activity showed that the community was able to process catfish into superior culinary products such as catfish pepes, crispy catfish, and frozen fillet catfish. In addition to improving skills, this activity also opens opportunities for the development of culinary tourism in the village. With the use of local resources, the community now has a new capacity to support sustainable culinary-based tourism. Keywords: tourism, culinary, processed catfish